İbn Teymiyye’nin tasavvuf’a bakışı - Terzi, Mesut (My University, 2014)
İBN TEYMİYYE’NİN TASAVVUF’A BAKIŞI “İbn Teymiyye’nin tasavvufa bakışı” adlı bu çalışmamızda ünlü âlim ve düşünür İbn Teymiyye’nin İslâm tasavvufuna bakışını ele aldık. Çalışmamızın birinci bölümünde onun hayatını, eserlerini ve görüşlerini anlattık. Bu çalışmada tasavvufu felsefî/ sistematik ve amelî/ ahlâkî olarak ikiye ayırdık. Zira çalışma ve araştırmalarımızda onun tasavvufu bütüncül bakış yerine nazarî ve amelî diye ayırarak değerlendirmelerini buna göre yaptığını gördük. Araştırmamızın ikinci bölümünde felsefî/ sistematik tasavvufun varlık anlayışı bağlamında Allah (Tevhid), Evren ve İnsan anlayışlarını ele aldık. Aynı bölümde felsefî/ sistematik tasavvufun Keşf ve İlhama dayanan bilgi anlayışını incelemeye çalıştık. Tasavvuf denince ilk akla gelen kısım olan ve bu tür çalışmalarda ihmal edilmemesi gereken amelî/ ahlâkî tasavvufa bakışını da yine bu bölümde tetkik etmeye çalıştık. Bu çerçevede amelî/ ahlâkî tasavvufun önemli kavramlarından olan zühd ve vera’, halvet ve riyâzet, fenâ’ ve bekâ, hâl ve makamlar, zikir, kerâmet ve semâ’ gibi konuları ele aldık. Sonuç ve değerlendirmede ise çalışma neticesinde vardığımız kanaati okuyucuya sunmaya çalıştık.

eğerlendirmede ise çalışma neticesinde vardığımız kanaati okuyuca sunmaya bakışını ele almaya öalıştık IBN TAYMIYYA'S VIEW ON TASAWWUF This study entitled “Ibn Taymiyya's View on Tasawwuf” discusses the renowned scholar and intellectual, Ibn Taymiyya, and his views regarding Islamic sufism. The first section of our study recounts his life, works, and views. This study divides sufism into two: the philosophical/ systematic and the practical/ ethical. Likewise, in our study and research we observe that Ibn Taymiyya carries out his analyses by dividing tasawwuf into theory and practice instead of assessing it holistically. The second part of our research examines the understandings of Allah (Tawhid), the universe, and the human being within the context of sufism's philosophical/ systematic conception of existence. In the same section, we attempted to examine sufism's philosophical/ systematic understanding of knowledge which is based on Kashf and Ilham. Again in this section, we aim to investigate that which first comes to mind when mentiong tasawwuf, and which also must not be ignored in these types of studies, that is to say, the practical and ethical view of tasawwuf. In this framework, we discuss important concepts of practical/ ethical tasawwuf, such as, ascetiscm (zuhd) and piety (wara'), seclusion (khalwah) and mortification (riyâdiyyah), annihilation of the self (fena') and abiding in God (baqa'), status (hâl) and stations (maqâm), miraculous deeds (karâmah) and spiritual listening (sama'). As for the conclusion and evaluation, at the end of our work we try to present to the reader our scholarly opinion.
Keywords: Felsefii Açıdan; Görüşleri; İbn Teymiyye; İbn Teymiyye, d. 1263- 1328; İslam Dini; İslam Felsefesi; Kelam; Tasavvuf; Türkiye